Analysis of Energy Absorption Device Operation in Changsha Metro Line 1 - Zhangshuo PENG; Bin YANG; Yong CHEN; Wei WAN (机车电传动)
According to the performance and configuration of the regenerated energy absorption device for Changsha metro line 1, 8 different patterns of devices were set up and tested. By comparing the experimental data, the energy-saving situation of each operation mode was obtained. At the same time, the reactive power output function of the regenerated energy absorption device was tested. Experiments showed that the energy-saving effect of regenerated energy absorption device is obvious when it is running, which reduces the energy consumption of brake resistance and has the function of reactive power output. It provided a reference value for the relevant design schemes in the subsequent construction lines.